The Cost Leadership, Entrepreneurship Orientation, and Differentiation Strategies of Bali's MSME in Tourism Sector - Dewangga, Made Agung Kori Wirya; Layman, Chrisanty Victoria (APMBA (Asia Pacific Management and Business Application), 2023)
This study aims to examine the impact of business orientation on performance, mediated by cost leadership and differentiation strategies of MSMEs in Bali's tourism sector during the COVID-19 pandemic- 19. The recovery of MSMEs in Bali has been promising due to the high demand for holiday by tourists. This study conducted a quantitative study with randomly sampled 200 respondents by filling the questionnaires to explore the correlation between business orientation and performance Data analysis was performed using Partial least squares Structural Equation Modeling (PLS-SEM) using SmartPLS application version 4.0.8.9. The results show that business orientation has a positive impact on cost leadership strategy, business orientation has a positive impact on differentiation strategy, business orientation has a positive impact on performance. , cost leadership strategy has a positive effect on performance, differentiation strategy has a positive effect on performance, business orientation has a positive effect on performance through cost leadership strategy cost, business orientation has a positive effect on performance through differentiation strategy.Â